Prevalence and risk factors of zoonotic helminth infection in domestic shorthair pet cats in Kuala Pilah / Mohamad Amirul Hafis Mohamad Hatta - Mohamad Hatta, Mohamad Amirul Hafis (2018)
House cat also called domestic cat (Felis catus) are pets that are scattered throughout the world and can play a role in the spread of various types of parasitic diseases including parasitic worms. The objective of this study was to identify the type of zoonotic helminth infection that prevalence in domestic shorthair pet cats in Kuala Pilah and to determine the relationship between the risk factors and the incidence rate of zoonotic helminth infection. The study design of this study is an observation base on the cross-sectional study that uses two types of data, that is the result of examination of the feces sample by centrifugal fecal floatation technique and microscopy in the laboratory and questionnaire data on the cat owners, then the data obtained from this study were analyzed using the Chi-square test and the odds ratio value estimation. The results of 50 samples of pet feces in Kuala Pilah showed that the prevalence of zoonotic helminth infections was 66%, where only hookworm type of helminth has been identified in pet cat feces in Kuala Pilah. Conclusion, the risk factors that have the significant relationship with the incidence rate of zoonotic helminth infection include gender of cats, providing and cleaning the cage, providing commercial sand for defecation, deworming of the cats, and eating habit of cats.